ACHIEVING ALTERNATIVES TO WRITTEN AND ORAL TRANSLATION PROCESSES FOR ENHANCED ACCURACY AND EFFICIENCY - Jumaeva Muhabbat Mustakimovna (American Journals Publishing, 2024)
This article explores alternatives to traditional written and oral translation processes to enhance accuracy and efficiency. It begins by differentiating between written translation, where both the original and translated texts are printed, allowing for extensive revisions, and oral translation, which involves transferring the main meaning of spoken statements between languages in real-time without the opportunity for corrections. The article examines various types of translation, including successive, visual, and simultaneous, and discusses their distinct characteristics. It highlights the classical classification of translation into written and oral types and elaborates on their specific processes and challenges. The analysis reveals significant differences in the form and execution of written and oral translations, emphasizing the limitations and strengths of each. The article also discusses the potential of visual translation and the use of speech-to-text software to streamline translation tasks. This innovative approach aims to reduce the mechanical workload of typing, thereby enhancing the efficiency of written translation. By comparing the cognitive processes involved in both translation types, the article underscores the importance of psychological factors and suggests ways to improve translation practices through technological advancements. The findings offer insights into achieving more effective and accurate translations, benefiting both translators and their clients.
Keywords: Oral translation, written translation, cognitive processes, adequacy, equivalence.